ISOLASI DAN SKRINING BAKTERI ASAM LAKTAT PROTEOLITIK FESES LUWAK PANDAN (Paradoxurus hermaphroditus) KALIMANTAN BARAT - Hasibuan, Rizki Permata Sari (BUANA SAINS, 2023)
The aimed of this study was to obtain lactic acid bacteria in civet feces used for the coffee fermentation process. This research was carried out isolation and screening of microbes specifically for proteolytic lactic acid bacteria. The bacterial isolation process using a selective MRS (Man Ragosa Sharpe) Agar medium and a bacterial screening process using Skim Milk Agar medium added with CaCO3. The results showed that 3 of the 12 isolated bacterial isolates could produce acid and protease: BAL 05, BAL 08, and BAL 09.